Safety and Immunogenicity of a Novel Recombinant Simian Adenovirus ChAdOx2 as a Vectored Vaccine - Folegatti, P; Bellamy, D; Roberts, R; Powlson, J; Edwards, N; Mair, C; Bowyer, G; Poulton, I; Mitton, C; Green, N; Berrie, E; Lawrie, A; et al. (MDPI, 2019)
Adenovirus vectored vaccines are a highly effective strategy to induce cellular immune responses which are particularly effective against intracellular pathogens. Recombinant simian adenovirus vectors were developed to circumvent the limitations imposed by the use of human adenoviruses due to widespread seroprevalence of neutralising antibodies. We have constructed a replication deficient simian adenovirus-vectored vaccine (ChAdOx2) expressing 4 genes from the Mycobacterium avium subspecies paratuberculosis (AhpC, Gsd, p12 and mpa). Safety and T-cell immunogenicity results of the first clinical use of the ChAdOx2 vector are presented here. The trial was conducted using a 'three-plus-three' dose escalation study design. We demonstrate the vaccine is safe, well tolerated and immunogenic.